2010
DOI: 10.1186/1471-2180-10-284
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium leguminosarum bv. trifolii rosR is required for interaction with clover, biofilm formation and adaptation to the environment

Abstract: BackgroundRhizobium leguminosarum bv. trifolii is a symbiotic nitrogen-fixing bacterium that elicits nodules on roots of host plants Trifolium spp. Bacterial surface polysaccharides are crucial for establishment of a successful symbiosis with legumes that form indeterminate-type nodules, such as Trifolium, Pisum, Vicia, and Medicago spp. and aid the bacterium in withstanding osmotic and other environmental stresses. Recently, the R. leguminosarum bv. trifolii RosR regulatory protein which controls exopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 78 publications
(114 reference statements)
6
50
0
Order By: Relevance
“…Previously, it was observed that the pssA mutant totally defective in EPS synthesis induced almost empty nodules inefficient in nitrogen fixation. Additionally, the rosR mutant produced 3-fold less EPS and elicited significantly fewer nodules, which were occupied by ten times fewer bacteria than the wild-type strain (Janczarek et al 2009a(Janczarek et al , 2010. The part-after-part estimation of the several enzymatic as well as non-enzymatic biochemical and physiological features of the wild-type and the pssA and rosR mutants cultured under oxidative stress conditions confirmed the crucial role of these genes involved in EPS synthesis in oxidative stress defence mechanisms.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previously, it was observed that the pssA mutant totally defective in EPS synthesis induced almost empty nodules inefficient in nitrogen fixation. Additionally, the rosR mutant produced 3-fold less EPS and elicited significantly fewer nodules, which were occupied by ten times fewer bacteria than the wild-type strain (Janczarek et al 2009a(Janczarek et al , 2010. The part-after-part estimation of the several enzymatic as well as non-enzymatic biochemical and physiological features of the wild-type and the pssA and rosR mutants cultured under oxidative stress conditions confirmed the crucial role of these genes involved in EPS synthesis in oxidative stress defence mechanisms.…”
Section: Discussionmentioning
confidence: 61%
“…Our previous studies indicated that mutations in rosR and pssA genes resulted in several pleiotropic effects, among them disturbances in membrane integrity causing unspecific protein leakage (Janczarek et al 2009a(Janczarek et al , 2010. Therefore, the levels of both extracellular and intracellular SOD activity have been determined.…”
Section: The Effect Of Mq and H 2 O 2 Treatment On Sod Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Like the BatR/BatS system, other transcriptional regulators have been hit in the STM screens and may thus participate in coordinating the expression of the huge arsenal of Bartonella virulence factors. One of those, RosR (374), is well known to be essential for productive host interaction in other Rhizobiales such as Sinorhizobium (207).…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…In R. leguminosarum bv. trifolii, the pssA gene is positively regulated by the transcriptional regulator RosR (15). Mutants of rosR have phenotypes similar to those described for chvG, including alterations in membrane stability, decreased levels of ropB expression, and symbiotic defects, suggesting that there may be overlap between the regulons of ChvG/ChvI and RosR (16).…”
Section: Discussionmentioning
confidence: 92%